2013
DOI: 10.1523/jneurosci.4790-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Arctigenin Effectively Ameliorates Memory Impairment in Alzheimer's Disease Model Mice Targeting Both  -Amyloid Production and Clearance

Abstract: Alzheimer's disease (AD) chiefly characterizes a progressively neurodegenerative disorder of the brain, and eventually leads to irreversible loss of intellectual abilities. The β-amyloid (Aβ)-induced neurodegeneration is believed to be the main pathological mechanism of AD, and Aβ production inhibition or its clearance promotion is one of the promising therapeutic strategies for anti-AD research. Here, we report that the natural product arctigenin from Arctium lappa (L.) can both inhibit Aβ production by suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(118 citation statements)
references
References 69 publications
2
116
0
Order By: Relevance
“…Primary cortical neuron culture Primary neuronal cultures from embryonic mouse brains (embryonic d 16 to 18) were created according to the approach described in the literature [12] . Briefly, cerebral cortices were separated from the brain, minced into small pieces, digested with D-Hanks buffer (5.4 mmol/L KCl, 0.41 mmol/L KH 2 PO 4 , 138 mmol/L NaCl, 4.5 mmol/L NaHCO 3 , 0.22 mmol/L Na 2 HPO 4 , pH 7.4) containing 0.125% trypsin and 200 U/mL DNase (Sigma-Aldrich, St Louis, MO, USA) and then incubated for 15 min at 37 °C, followed by mechanical dissociation by pipetting in DMEM with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…Primary cortical neuron culture Primary neuronal cultures from embryonic mouse brains (embryonic d 16 to 18) were created according to the approach described in the literature [12] . Briefly, cerebral cortices were separated from the brain, minced into small pieces, digested with D-Hanks buffer (5.4 mmol/L KCl, 0.41 mmol/L KH 2 PO 4 , 138 mmol/L NaCl, 4.5 mmol/L NaHCO 3 , 0.22 mmol/L Na 2 HPO 4 , pH 7.4) containing 0.125% trypsin and 200 U/mL DNase (Sigma-Aldrich, St Louis, MO, USA) and then incubated for 15 min at 37 °C, followed by mechanical dissociation by pipetting in DMEM with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…Huperzine A [326,327] , 2,2',4'-trihydroxychalcone (TDC) [328] and bis(7)-cognitin [329] exhibit neuroprotective effects. Agenin [330] and clioquinol [331] can inhibit Aβ deposition. Other inhibitors, such as the RAGE inhibitor azeliragon, the α7-nAChR inhibitor encenicline and the calcium antagonist nilvaldipine, can improve memory and could be further candidates for Alzheimer's disease therapeutics [332][333][334] (Table 9).…”
Section: Therapies Directed Against the Tau Proteinmentioning
confidence: 99%
“…It has been suggested that AR possesses anti-viral (1-3), anti-inflammation (4-6), and immunomodulation effects (7) in a variety of in vitro and in vivo models. It was also demonstrated, in a diseased mice model, that AR had potential as a drug candidate for the treatment of Alzheimer's disease through targeting β-amyloid formation and clearance, with the effect of ameliorating memory impairment (8). However, the most extensively studied therapeutic aspect of AR is its anti-cancer activity, resulting in the launch of its phase I and II clinical trials, in which AR was used as the second-line therapeutic agent for the treatment of pancreatic cancer (9).…”
Section: Introductionmentioning
confidence: 99%